Cost Modeling of Geometrical Quality in Mega-cast Rear Floors - Haglund, Alexander; Cederqvist, Filip (My University, 2025)
This thesis investigates the geometrical quality of mega-cast rear floors in automotive manufacturing and its associated cost implications. The study has three main objectives: to evaluate and compare the geometrical quality of different rear floor concepts, to identify and assess methods for improving geometrical quality in megacast rear floors, and to develop a cost model that quantifies the cost of geometrical quality in mega-cast rear floors. A combination of statistical data analysis, literature review, expert interviews, simulation, and cost modeling was used to achieve these aims. Several statistical analysis tests were conducted to compare the geometrical quality of the different rear floor concepts. Further, a variety of methods and processes for improving the geometrical quality of the mega-cast rear floor was identified. Lastly, a cost model was developed to quantify the cost of geometrical quality for mega-cast rear floors. A separate simulation model was also set up to calculate costs arising from geometrical deviations and to serve as input for the cost model. The models were applied in different contexts including some of the most promising process improvements. The results of the applied methodology have provided insights into the importance of geometrical quality and its impact on cost. However, in some cases, a lack of data has introduced a degree of uncertainty into the results, making definitive conclusions difficult to draw. The methodology remains suitable for future use and is expected to yield clearer results as data quality improves
Keywords: mega-casting; geometrical quality; cost; modeling; high pressure die casing; cost simulation